Islamic law for water and land management and its impact on urban morphology - Ben-Hamouche, Mustapha (2008)
Urban morphology and territorial landscape of Islamic cities were deeply affected by the Islamic law that regulated the ownership, distribution and use of water and land. Due to the climatic exigencies and the economy of subsistence that was mostly based on agriculture, water was a precious liquid that was treated with special care. A sophisticated system of subdivision of shares was developed by jurists from the succession law and right of ownership over a long history of daily practices and cumulated body of legal opinions. Consequently, the analysis of urban forms in Muslim cities cannot bypass the study of these mechanisms that are found in books of jurisprudence, archives and courts records and the people’s practices that are rooted in the local traditions and that are still standing in some parts of the Muslim world. The present study aims at presenting these mechanisms and shade light on their physical impact in the Muslim cities. The complex geometry of land subdivision in both urban and rural areas, and water irrigation system are analyzed through the available maps and aerial views. Cities such as Blida, Kolea and Tamentit, Algeria, provide sufficient documents for the study of this relationships between the Islamic law and the urban form and thus, serve as case studies. The study aims at presenting a good example of the interaction between human needs, faith and spirituality, and laws of nature, and thus add a new dimension to the concept of sustainability.